Trade openness reduces growth volatility when countries are well diversified - Mona Haddad; Jamus Jerome Lim; Cosimo Pancaro; Christian Saborowski (European Central Bank (ECB), 2012)
This paper addresses the mechanisms by which trade openness affects growth volatility. Using a diverse set of export concentration measures, we present strong evidence pointing to an important role for export diversification in conditioning the effect of trade openness on growth volatility. Indeed, the effect of openness on volatility is shown to be negative for a significant proportion of countries with relatively diversified export baskets.
Keywords: F15; F43; O24; 330; Export diversification; growth volatility; trade openness; Internationale Wirtschaft; Exportdiversifizierung; Wirtschaftswachstum; Volatilität; Welt